1992
DOI: 10.1037/0882-7974.7.3.376
|View full text |Cite
|
Sign up to set email alerts
|

Aging, expertise, and narrative processing.

Abstract: In a study of how aviation expertise influences age differences in narrative processing, young and older pilots and nonpilots read and recalled aviation and general narratives. They chose referents for sentences referring to a protagonist or minor character mentioned 1 sentence (recent character) or 3 sentences (distant character) before this target sentence. All groups chose referents less accurately for sentences about distant and minor characters than about recent and protagonist characters, perhaps because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
61
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 43 publications
13
61
1
Order By: Relevance
“…The studies discussed above demonstrated that younger and older adults tend to integrate information into the causal structure of the situation model (Radvansky, Copeland, & Zwaan, 2003). They also represent prominent and integral components of the situation model in a similar manner (Morrow et al, 1992). Likewise, younger and older adults display similar temporal updating when there is a substantial time shift in the narrative and spatial updating that involves changes in the availability of an object relative to the protagonist (Morrow et al, 1997;Stine-Morrow et al, 2002).…”
Section: Age-invariant Cognitionmentioning
confidence: 87%
See 1 more Smart Citation
“…The studies discussed above demonstrated that younger and older adults tend to integrate information into the causal structure of the situation model (Radvansky, Copeland, & Zwaan, 2003). They also represent prominent and integral components of the situation model in a similar manner (Morrow et al, 1992). Likewise, younger and older adults display similar temporal updating when there is a substantial time shift in the narrative and spatial updating that involves changes in the availability of an object relative to the protagonist (Morrow et al, 1997;Stine-Morrow et al, 2002).…”
Section: Age-invariant Cognitionmentioning
confidence: 87%
“…In a conceptually related study by Morrow, Leirer, and Altieri (1992), younger and older adults read a series of passages in which there were protagonists as well as minor characters. What was observed was that although there was an age difference in the ability to resolve anaphors that referred to minor characters, there was no such age effect for the protagonist.…”
Section: Model Creationmentioning
confidence: 99%
“…In the other, lengthy interruptions were introduced to disrupt movement down the street. The focus on distraction was prompted by numerous findings that older persons are more affected by irrelevant stimuli than younger persons in complex visual search environments (Carlson, Hasher, Connelly, & Zacks, 1995;Morrow, Leirer, & Altieri, 1992;Plude & Hoyer, 1986;Rabbitt, 1965), possibly as a consequence of an inability to inhibit irrelevant inputs (Hasher & Zacks, 1988).…”
Section: Studymentioning
confidence: 99%
“…Although aging represents more than declines in WM, these declines represent a major feature of age-related cognitive change. Several researchers have reasoned that, due to age-related declines in WM, knowledge could be more important with increasing age (e.g., Arbuckle, Vanderleck, Harsany, & Lapidus, 1990;Hultsch & Dixon, 1983;Miller, 2001Miller, , 2003Miller & Stine-Morrow, 1998;Miller, Stine-Morrow, Kirkorian, & Conroy, 2004;Morrow, Leirer, & Altieri, 1992;Morrow, Leirer, Altieri, & Fitzsimmons, 1994).…”
mentioning
confidence: 99%